Agricultura orgânica do estado do Espírito Santo : diversidade e comercialização de seus produtos na região metropolitana de Vitória - Sposito, Elaine Caliman (2015)
This study presents an analysis of the diversity of forms on organic food production commercialization in Vitoria (ES), and the discussion about this research theme. The goal is to understand how and under which conditions the market valorizes the local production, strengthening the ecological family production and the food sovereignty. The research methodology took into consideration quantitative and qualitative data, utilizing available public information and data acquired in field research. The evaluation shows that organic products are commercialized by direct sales, in organic outdoor markets and fair markets, and by indirect sales in supermarkets, specialized stores and restaurants. Among the evaluated commercialization channels, were the organic product outdoor markets that showed a greater product diversity, in addition to a better price, which were up to five times lower than in the supermarkets. Furthermore, organic product prices, when compared to the equivalent conventional ones, always showed higher values in indirect sales. However, among conventional and organic street markets, organic products prices were higher, equal or smaller than their conventional equivalents. Therefore, it concludes that this commercialization channel valorizes the organic family production, promoting the empowerment of family producers and the access to healthful alimentation for local consumers.